Airflow disturbance induced by coal mine outburst shock waves: A case study of a gas outburst disaster in China - Zhou, Aitao; Zhang, Meng; Wang, Kai; Elsworth, Derek; Wang, Jiawen; Fan, Lingpeng (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2020)
We explore the magnitude of airflow disturbance in mine roadways induced by gas outburst shock waves. Outburst shock wave propagation in the near-field of the outburst source is established and simulated in three dimensions using FLUENT. The effects in connected but distal roadways are represented by a simplified one-dimensional network model and solved by Flowmaster. A Mesh-based Parallel Code Coupling Interface (MPCCI) is applied to couple the three-dimensional (near source) model and the one-dimensional (distal) model. The coupled model is verified by theoretical analysis and against observations from a coal and gas outburst incident comprising 2887 tonnes of coal that occurred in the Jiulishan coal mine, China and general characteristics of outburst events explored. Simulations demonstrate that airflow disturbance induced by outburst shock waves in the coal mine is principally controlled by the shock wave overpressure and fan pressure provided by the main fan. Of these, the shock wave overpressure exerts the dominant impact. The larger the shock-wave overpressure, the more rapid the decrease of airflow in the roadway branches and the larger the ultimate airflow decrease. Furthermore, the arrival time of the minimum air flow rate is delayed. When the fan pressure is large, the ability to resist airflow disturbance is enhanced and the area subject to countercurrent flow is reduced. The initial air flow rate and the restored air flow rate show less correlation with the shock wave overpressures. However, they are both significantly affected by the pressure of the main fan. This work presents a novel approach for the study of airflow disturbance in underground ventilation networks in coal mines caused by coal and gas outbursts and provides guidance for the design of outburst prevention facilities.